Pulsation Investigation of Underwater Hydrogen Explosion Products at Well Regeneration - V. V. Ivashechkin; V. V. Veremenuk; V. V. Gubin; A. N. Kondratovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A methodology and results of experimental pulsation investigations on products of underwater hydrogen-oxygen gas mixture explosion in cylindrical chambers which are open from the bottom and spherical chambers with elastic covers are provided in the paper. The paper contains a comparative analysis of experimental investigation results with theoretical calculations.